Suggested questions for non-computer science students' assessments using Bloom's taxonomy in programming context / Rozita Kadar, Saiful Nizam Warris and Syarifah Adilah Mohamed Yusoff - Kadar, Rozita; Warris, Saiful Nizam; Mohamed Yusoff, Syarifah Adilah (Unit Penerbitan JSKM, 2020)
Introduction to programming language is a course that offered to several programmes in UiTM. This course will emphasize on the introduction of computer problem solving with the use of C++ programming language to illustrate the solution. The aim is to develop students' problem-solving strategies, techniques and analytical skills that can be applied to computer field or in other areas as well as to use in their subsequent course work and professional development. Students are learned to identify a problem, design appropriate solution and solve the problem in computerized way. At the beginning, students are introduced to the basic elements in programming. At this stage, students able to declare variables, applying mathematical operation and able to construct a simple programming statement. Then, student will be exposed to the used of selection control structure and repetition control structure. The implementation of functions and array are also discussing in this course. At the end of semester, students are able to write a complete programming by applying all the elements that are discussed in the course.